Captation, storage and use of rainwater for non-drinking purposes (Research, Society and Development, 2020)
Although water occupies two thirds of the Earth's surface, it knows that only 2.5% of its volume is considered sweet and suitable for consumption. This being indispensable for economic development and the maintenance of life on the planet. However, the accelerated population increase, coupled with agricultural, industrial and technological development, presents increasing levels of avocado, water pollution levels and degradation of natural resources, posing a huge global threat regarding the use of permitted human resources and ensuring that future future enjoy drinking water with quality standards suitable for your consumption. In this context, the objective of this work is to present the system for capturing and using rainwater as a sustainable alternative to replace treated water in activities that are not potentially dangerous or involve risks to human health, thus allowing the way resources natural resources are affected less exploited, avoiding waste, minimizing environmental impacts, reducing energy consumption and expenses, generating savings in water and sewage bills, decreasing the demand for rain galleries and using the number of floods and floods.